Neuroprotection of cannabidiol in epileptic rats: Gut microbiome and metabolome sequencing - Gong, Xiaoxiang; Liu, Lingjuan; Li, Xingfang; Xiong, Jie; Xu, Jie; Mao, Dingan; Liu, Liqun (Frontiers in Nutrition, 2022)
Aims Epilepsy is a neurological disease occurring worldwide. Alterations in the gut microbial composition may be involved in the development of Epilepsy. The study aimed to investigate the effects of cannabidiol (CBD) on gut microbiota and the metabolic profile of epileptic rats. Materials and methods and results A temporal lobe epilepsy rat model was established using Li-pilocarpine. CBD increased the incubation period and reduced the epileptic state in rats. Compared to epileptic rats, the M1/M2 ratio of microglia in the CBD group was significantly decreased. The expression of IL-1β, IL-6, and TNF-α in the CBD group decreased, while IL-10, IL-4, and TGF-β1 increased. 16S rDNA sequencing revealed that the ANOSIM index differed significantly between the groups. At the genus level, Helicobacter, Prevotellaceae_UCG-001, and Ruminococcaceae_UCG-005 were significantly reduced in the model group. CBD intervention attenuated the intervention effects of Li-pilocarpine. Roseburia, Eubacterium_xylanophilum_group, and Ruminococcus_2 were strongly positively correlated with proinflammatory cytokine levels. CBD reversed dysregulated metabolites, including glycerophosphocholine and 4-ethylbenzoic acid. Conclusion CBD could alleviate the dysbiosis of gut microbiota and metabolic disorders of epileptic rats. CBD attenuated Epilepsy in rats might be related to gut microbial abundance and metabolite levels. Significance and impact of study The study may provide a reliable scientific clue to explore the regulatory pathway of CBD in alleviating Epilepsy.